Co-Evolution of Organizations in Infrastructure Planning: The Role of Communities of Practice as Windows for Collective Learning Across Project-Oriented Organizations. Issue 7 (August 2022) - de Groot, Bert; Leendertse, Wim; Arts, Jos
Challenges in infrastructure planning require public infrastructure administrators, responsible for providing adequate infrastructure facilities, to be adaptive. These organizations evolve and interact with other organizations in a complex organizational landscape. This paper explores the contribution of inter-organizational communities of practice (CoPs) to collective learning and co-evolution of organizations in infrastructure planning. We conducted a case study of five inter-organizational CoPs in the domain of a typical public infrastructure administrator. The results suggest that inter-organizational CoPs enable, for example, policy and practice to co-evolve. Inter-organizational CoPs seem to provide a neutral ground where long-term sector benefits can overcome short-term organizational interests.